Paricalcitol attenuates TGF‐β1–induced phenotype transition of human peritoneal mesothelial cells (HPMCs) via modulation of oxidative stress and NLRP3 inflammasome. Issue 2 (24th October 2018) - Ko, Jiyeon; Kang, Hyun-Jung; Kim, Dal-Ah; Ryu, Eun-Sun; Yu, Mina; Lee, Huisong; Lee, Hyeon Kook; Ryu, Hye-Myung; Park, Sun-Hee; Kim, Yong-Lim; Kang, Duk-Hee
ABSTRACT: Phenotype transition of mesothelial cells, such as epithelial‐to‐mesenchymal transition (EMT), is one of the early mechanisms of peritoneal fibrosis, which is mediated by oxidative stress and inflammation. Nucleotide‐binding oligomerization domain‐like receptor family pyrin domain containing 3 (NLRP3) inflammasome is a multiprotein oligomer that promotes the maturation of IL‐lβ and IL‐18. Paricalcitol is reported to exert an antiinflammatory effect; however, there are no studies as to whether paricalcitol modulates the activation of NLRP3 inflammasome. We investigated the role of NLRP3 inflammasome in peritoneal EMT with an exploration of the effect of paricalcitol on oxidative stress, NLRP3 inflammasome, and EMT of mesothelial cells. TGF‐βl‐induced EMT in human peritoneal mesothelial cells (HPMCs) was associated with an up‐regulation of NLRP3, apoptosis‐associated speck‐like protein containing a caspase recruitment domain (ASC), and ρrocasρase‐1, with an increased production of IL‐lβ and IL‐18, which was ameliorated by small interfering (si)NLRP3, siASC, caspase inhibitors, or neutralizing antibodies for IL‐lβ and IL‐18. TGF‐βl enhanced reactive oxygen species generation with an increase in NADPH oxidase (NOX) activity and mitochondrial NOX4 production. Paricalcitol alleviated TGF‐βl‐induced EMT and the NLRP3 inflammasome, which was associated with a down‐regulation of NOX activity by interfering with p47phox and p22phox interaction and mitochondrial NOX4 production in HPMCs. Taken together, paricalcitol ameliorated EMT of HPMCs via modulating an NOX‐dependent increase in the activity of NLRP3 inflammasome. Paricalcitol could be a novel approach to protect the peritoneum from the development of EMT and peritoneal fibrosis.—Ko, J., Kang, H.‐J., Kim, D.‐A., Ryu, E.‐S., Yu, M., Lee, H., Lee, H. K., Ryu, H.‐M., Park, S.‐H., Kim, Y.‐L., Kang, D.‐H. Paricalcitol attenuates TGF‐βl–induced phenotype transition of human peritoneal mesothelial cells (HPMCs) via modulation of oxidative stress and NLRP3 inflammasome. FASEB J. 33, 3035–3050 (2019). www.fasebj.org